Pengembangan Kawasan Danau Mawang sebagai Kawasan Ekowisata - Andi Muhammad Ansar; Mukti Ali; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Lake Mawang as ecotourism and scientific land will become a tourism icon in Gowa Regency. The lake, which is located between two sub-districts, namely Bontomarannu Subdistrict and Somba Opu Subdistrict, is one of the main program proposals in the Tourism Sector Potential Development and Rehabilitation program (Gowa District Regulation No.4 of 2007). In addition, based on the Gowa Regency RTRW in 2011-2030, Lake Mawang was designated as a District Strategic Area (KSK) for the benefit of environmental carrying capacity, which plays a role in the ecological utilization and balance of environmental preservation. The purpose of this study was to identify the potential and problems of the Mawang Lake area and formulate directions for developing the Mawang Lake area as an ecotourism area. The analysis technique used is the ODTW analysis to determine the value of potential development, the level of feasibility of tourist objects and attractions. Then consider the physical and non-physical aspects with a qualitative approach to identify potential and problems so that they can formulate the direction of developing ecotourism in the Mawang Lake area. The results of this study show that the ODTW evaluation interval of the Mawang Lake area is in the "good" interval to be developed, and the level of feasibility of objects and tourist attractions is in the "very potential" classification. The directives are in the form of ecotourism zoning planning, development of tourist attractions, circulation and transportation directions, planning of infrastructure facilities, increasing the capacity of stakeholders, and strategies in tourism promotion marketing.